Markers of oxidative stress during post-COVID-19 fatigue: a hypothesis-generating, exploratory pilot study on hospital employees - Hofmann, Hanna; Önder, Alexandra; Becker, Juliane; Gröger, Michael; Müller, Markus M.; Zink, Fabian; Stein, Barbara; Radermacher, Peter; Waller, Christiane (Frontiers in Medicine, 2023)
Introduction Post-COVID-19 fatigue is common after recovery from COVID-19. Excess formation of reactive oxygen species (ROS) leading to oxidative stress-related mitochondrial dysfunction is referred to as a cause of these chronic fatigue-like symptoms. The present observational pilot study aimed to investigate a possible relationship between the course of ROS formation, subsequent oxidative stress, and post-COVID-19 fatigue. Method A total of 21 post-COVID-19 employees of the General Hospital Nuremberg suffering from fatigue-like symptoms were studied during their first consultation (T1: on average 3 months after recovery from COVID-19), which comprised an educational talk on post-COVID-19 symptomatology and individualized outpatient strategies to resume normal activity, and 8 weeks thereafter (T2). Fatigue severity was quantified using the Chalder Fatigue Scale together with a health survey (Patient Health Questionnaire) and self-report on wellbeing (12-Item Short-Form Health Survey). We measured whole blood superoxide anion (O2•-) production rate (electron spin resonance, as a surrogate for ROS production) and oxidative stress-induced DNA strand breaks (single cell gel electrophoresis: “tail moment” in the “comet assay”). Results Data are presented as mean ± SD or median (interquartile range) depending on the data distribution. Differences between T1 and T2 were tested using a paired Wilcoxon rank sign or t-test. Fatigue intensity decreased from 24 ± 5 at T1 to 18 ± 8 at T2 (p < 0.05), which coincided with reduced O2•- formation (from 239 ± 55 to 195 ± 59 nmol/s; p < 0.05) and attenuated DNA damage [tail moment from 0.67 (0.36–1.28) to 0.32 (0.23–0.71); p = 0.05]. Discussion Our pilot study shows that post-COVID-19 fatigue coincides with (i) enhanced O2•- formation and oxidative stress, which are (ii) reduced with attenuation of fatigue symptoms.